2013
DOI: 10.3390/socsci2040221
|View full text |Cite
|
Sign up to set email alerts
|

The Eurozone Crisis: Muddling through on the Way to a More Perfect Euro Union?

Abstract: Taking a historical perspective of economic changes, this paper argues that muddling through crises-induced reforms characterizes well the evolutionary process of forming currency unions. The economic distortions facing the euro include structural challenges in the labor and product markets, and financial distortions. While both structural and financial distortions are costly and prevalent, they differ in fundamental ways. Financial distortions are moving at the speed of the Internet, and their welfare costs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This is the case because the forecasters have to provide their predictions at the beginning of the months (e.g., a prediction for the three month EURIBOR at the end of March 2013 had to be provided already in December 2012). The evaluated sample ranges from December 1998 to March 2013 and because of that covers both the subprime crisis in 2007/08 and the following financial turmoil resulting in the European sovereign debt crisis (e.g., Aizenman, 2013;Basse et al, 2013). As a matter of fact the data in the first part of the series implies that there should be no structural breaks due to the common European currency area starting 1999.…”
Section: Methodsmentioning
confidence: 99%
“…This is the case because the forecasters have to provide their predictions at the beginning of the months (e.g., a prediction for the three month EURIBOR at the end of March 2013 had to be provided already in December 2012). The evaluated sample ranges from December 1998 to March 2013 and because of that covers both the subprime crisis in 2007/08 and the following financial turmoil resulting in the European sovereign debt crisis (e.g., Aizenman, 2013;Basse et al, 2013). As a matter of fact the data in the first part of the series implies that there should be no structural breaks due to the common European currency area starting 1999.…”
Section: Methodsmentioning
confidence: 99%
“…Javer et al (2014) suggested that the migration response to the crisis has been considerable in Europe, as suggested in the OCA and compared to the USA, where the crisis and sluggish recovery were not accompanied by interregional labour mobility in reaction to labour market shocks. Conversely, Aizenman (2014) suggested that all estimated labour migration (upper bound) can be absorbed up a quarter of the asymmetric labour market shock, although thirdcountry migrants and lower mobility of the capital market are suggested as alternative solutions. This can be maintained until effective financial and labour institutions are enlarged throughout the euro area, which is supported in this study.…”
Section: European Monetary Unionmentioning
confidence: 99%
“…However, in a given scenario, Polish workers may move to Germany, but because of the rigidity of the labour market and qualification differences between workers, the interregional integration of member countries is reduced, and this reduces the absorption of asymmetric shocks. Aizenman (2014) JEAS 37,1 suggested that all estimated labour migration up to about a quarter of the asymmetric labour market shock would be absorbed. While this may appear unreasonable based on the conventional wisdom that inflation usually affects the economy in a negative way, except for the short-run application, in Poland, inflation and devaluation are considered as a model for developing the economy.…”
Section: Interpretation Of Estimated Data For Polandmentioning
confidence: 99%
“…In the past, SCR was mainly a problem for less-developed countries, although recently it has also become an issue for EMU member countries (Aizenman, 2013; Moro, 2014). Meanwhile, oil-producing countries also have to cope with this problem, as stated by Wegener et al (2016).…”
Section: Literature Overview and History Of The Euro Crisismentioning
confidence: 99%